(untitled) (Applied Biological Research, 2023)
The present study was aimed to evaluate the antidiabetic and antioxidant activities of a lactic acid bacterial strain ‘Lactobacillus casei NCDC 357’, and to investigate its probiotic characteristics. The antidiabetic activity was examined by evaluating the α-glucosidase and α-amylase inhibitory activities. L. casei strain NCDC 357 exhibited antidiabetic activities by α glucosidase (67.7% and IC50 38.08 μL) and α-amylase (53.6% and IC50 49.96 μL). The strain showed antioxidant activities by DPPH (53.4% and IC50 77.60 μL) and ABTS (48.7% and IC50 51.48 μL). Further, the strain was resistant to simulated gastrointestinal juice and showed potential for health promotiobased on adhesion, antibiotic susceptibility, and anti microbial activities. L. casei NCDC 357 appeared to be a potential probiotic having beneficial health effects.